2018
DOI: 10.1080/00207454.2017.1403915
|View full text |Cite
|
Sign up to set email alerts
|

Effects of virtual reality-based training with BTs-Nirvana on functional recovery in stroke patients: preliminary considerations

Abstract: According to these preliminary data, VRT with I-SIP can be considered a useful complementary treatment to potentiate functional recovery, with regard to attention, visual-spatial deficits, and motor function in patients affected by stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 25 publications
2
90
1
Order By: Relevance
“…Moreover, only VRTG improved in specific cognitive domains, such as cognitive flexibility, attentional shifting, visual search, and executive and visuospatial functions, that are necessary for planning and managing daily life. Thus, VR can be considered a useful tool for patients with TBI, as demonstrated in various neurological disorders by previous studies [2833]. Indeed, it has been shown that VRT is effective in enhancing attention, visual-spatial capacity, and motor function in patients with stroke [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, only VRTG improved in specific cognitive domains, such as cognitive flexibility, attentional shifting, visual search, and executive and visuospatial functions, that are necessary for planning and managing daily life. Thus, VR can be considered a useful tool for patients with TBI, as demonstrated in various neurological disorders by previous studies [2833]. Indeed, it has been shown that VRT is effective in enhancing attention, visual-spatial capacity, and motor function in patients with stroke [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…In the last years there has been significant growth in the evidence for post-stroke cognitive rehabilitation [12,13], with a number of studies proposing ecologically valid VR-based simulations of ADL's as the most promising training solutions [26,27]. Notwithstanding the advantages of VR, there are several areas that require further progress.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last years, rehabilitation methodologies based on virtual reality (VR) have been developed as promising solutions to improve cognitive functions [26,27]. VRbased tools have shown potential and to be ideal environments to incorporate cognitive tasks within the simulation of ADL's [28].…”
Section: Is Cognitive Rehabilitation's Impact Small or Are We Missingmentioning
confidence: 99%
“…Cognition refers to the mental processes associated with processing information and responding with appropriate actions. 81 Cognitive impairment is a common effect of neurodegenerative diseases, traumatic brain injuries, and stroke and can lead to reduced ability to perform self-care tasks and participate in social and community activities. Different multistimuli therapeutic VR systems, for example, BTS-Nirvana 82 and VRROOM 83 have been tested in attempts to provide relaxation, or as tools for attention and memory training in traumatic brain injury and stroke patients.…”
Section: Vr In Psychiatry and Medicine Todaymentioning
confidence: 99%